Problem of understanding in course of theories of sense and meaning (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the classic and modern theories of sense and meaning. The philosophical root of such theories is considered. Some distinctive features of sense and meaning are ascertained. Basic achievements of modern theories of sense and meaning are determined, and possibility of the use of these theories for deep research of problem of understanding.
Keywords: sense; meaning; understanding